The Evolutionary Patterns of Genome Size in Ensifera (Insecta: Orthoptera) - Yuan, Hao; Huang, Yuan; Mao, Ying; Zhang, Nan; Nie, Yimeng; Zhang, Xue; Zhou, Yafu; Mao, Shaoli (Frontiers in Genetics, 2021)
Genomic size variation has long been a focus for biologists. However, due to the lack of genome size data, the mechanisms behind this variation and the biological significance of insect genome size are rarely studied systematically. The detailed taxonomy and phylogeny of the Ensifera, as well as the extensive documentation concerning their morphological, ecological, behavioral, and distributional characteristics, make them a strong model for studying the important scientific problem of genome size variation. However, data on the genome size of Ensifera are rather sparse. In our study, we used flow cytometry to determine the genome size of 32 species of Ensifera, the smallest one being only 1C = 0.952 pg with the largest species up to 1C = 19.135 pg, representing a 20-fold range. This provides a broader blueprint for the genome size variation of Orthoptera than was previously available. We also completed the assembly of nine mitochondrial genomes and combined mitochondrial genome data from public databases to construct phylogenetic trees containing 32 species of Ensifera and three outgroups. Based on these inferred phylogenetic trees, we detected the phylogenetic signal of genome size variation in Ensifera and found that it was strong in both males and females. Phylogenetic comparative analyses revealed that there were no correlations between genome size and body size or flight ability in Tettigoniidae. Reconstruction of ancestral genome size revealed that the genome size of Ensifera evolved in a complex pattern, in which the genome size of the grylloid clade tended to decrease while that of the non-grylloid clade expanded significantly albeit with fluctuations. However, the evolutionary mechanisms underlying variation of genome size in Ensifera are still unknown.